Silicon microgrooves for contact guidance of human aortic endothelial cells - Fernández-Castillejo, Sara; Formentín, Pilar; Catalán, Úrsula; Pallarès, Josep; Marsal, Lluís F.; Solà, Rosa (Beilstein Journal of Nanotechnology, 2017)
Background: Micro- and nanoscale substrates have been fabricated in order to study the influence of the topography on the cellular response. The aim of this work was to prepare different collagen-coated silicon substrates displaying grooves and ridges to mimic the aligned and elongated endothelium found in linear vessels, and to use them as substrates to study cell growth and behaviour.Results: The influence of groove-shaped substrates on cell adhesion, morphology and proliferation were assessed, by comparing them to flat silicon substrates, used as control condition. Using human aortic endothelial cells, microscopy images demonstrate that the cellular response is different depending on the silicon surface, when it comes to cell adhesion, morphology (alignment, circularity and filopodia presence) and proliferation. Moreover, these structures exerted no cytotoxic effect.Conclusion: The results suggest that topographical patterning influences cell response. Silicon groove substrates can be used in developing medical devices with microscale features to mimic the endothelium in lineal vessels.
Keywords: cell morphology; contact guidance; microgrooves; silicon; human aortic endothelial cells (HAECs)